Predictors of subjective well-being of parents and children/ adolescents during COVID-19’s first wave in Portugal - Ramos, A.; Tendais, I.; Rodrigues, R. B.; Costa, L.P.; Alvarez, E. (European Survey Research Association, 2021)
Subjective well-being has been seriously challenged during the COVID-19 pandemic. The lack of a vaccine and appropriate treatment for the disease, the rapid spread across countries, and the unpredictability of the outcome has led to the adoption of restrictive public health measures, namely school closure and home confinement. The nature of the disease (e.g., highly contagious, unpredictable, long-term sequelae) and the measures adopted to tackle it have contributed to the appearance or the aggravation of pre-existing mental health problems. Parents and children/ adolescents, in particular, have been significantly affected by one of the public health measures adopted in several countries during emergency state lockdowns - school and activity centers closure. In Portugal, schools were closed from mid-March from 2020 until the end of the academic year. As part of a larger study on the social development of human values in childhood and early adolescence, an online survey was carried out from May 25 to July 13, 2020, to examine the subjective well-being of parents and children/ adolescents during the first wave of the COVID-19 pandemic. A sample of 2385 parents and 1744 children/ adolescents (from 6 to 14 years) participated in the study and completed measures of several dimensions of well-being, including life satisfaction, emotional well-being, and perceived health status. The findings show that parental well-being was explained by individual, relational, and school-related variables, including sociodemographic variables, risk perception of COVID-19, pre-COVID satisfaction with life, personal values, personal and child-related difficulties, child well-being, amount of homework, satisfaction with close relationships, and interpersonal and institutional trust. Regarding child/ adolescent well-being, it was mostly explained by parental and school-related variables, namely the well-being and values of the parent; amount, difficulties and assistance on school-related work; child-related difficulties; and, satisfaction with friendship relationships. Taking care of a pet was also related to child/ adolescent well-being. These variables explained 34% to 40% of subjective well-being. These results highlight the importance that school-related factors had to both parental and child/ adolescent well-being during a time when schools were closed.